Efficiency improving fossil fuel technologies for electricity generation: Data selection and trends - Elisa Lanzi; Elena Verdolini; Ivan Haéscic (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper studies innovation dynamics in efficiency improving electricity generation technologies as an important means of mitigating climate change impacts. Relevant patents are identified and used as an indicator of innovation. We find that patenting in efficiency improving technologies has mostly been stable over time, with a recent decreasing trend. We also find that majority of patents are first filed in OECD countries and only then in non-OECD or BRIC countries. Conversely, non-OECD and BRIC countries apply for patents that are mostly marketed domestically. This result shows that there is significant technology transfer in the field of efficiency improving technologies for electricity production. This flow of know-how is likely to contribute to mitigation of greenhouse gases emissions in emerging economies in the long run.
Keywords: Q32; Q4; Q55; 330; Climate Change; Technological Innovation; Energy; Patents; Fossil Fuels